Evaluation of the rat tissue reaction to experimental new resin cement and mineral trioxide aggregate cement - Won-Kyung Yang; Hyun-Jung Ko; Mi-Ri Kim (Korean Academy of Conservative Dentistry, 2012)
Objectives New resin cement (NRC) has been developed as a root repairing material and the material is composed of organic resin matrix and inorganic powders. The aim of this study was to compare the rat subcutaneous tissue response to NRC and mineral trioxide aggregate (MTA) cement and to investigate the tissue toxicity of both materials. Materials and Methods Sixty rats received two polyethylene tube-implants in dorsal subcutaneous regions, MTA and NRC specimens. Twenty rats were sacrificed respectively at 1, 4 and 8 wk after implantation and sectioned to 5 µm thickness and stained with Hematoxylin-Eosin (H-E) or von-Kossa staining. The condition of tissue adjacent to the implanted materials and the extent of inflammation to each implant were evaluated by two examiners who were unaware of the type of implanted materials in the tissues. Data were statistically analyzed with paired t-test (p < 0.05). Results In specimens implanted with both NRC and MTA, severe inflammatory reactions were present at one wk, which decreased with time. At eighth wk, MTA implanted tissue showed mild inflammatory reaction, while there were moderate inflammatory reactions in NRC implanted tissue, respectively. In NRC group, von-Kossa staining showed more calcification materials than MTA group at eighth wk. Conclusions It was concluded that the calcium reservoir capability of NRC may contribute to mineralization of the tissues.